Unlocking the potential of Kluyveromyces marxianus in the definition of aroma composition of cheeses - Perpetuini, Giorgia; Rossetti, Alessio Pio; Rapagnetta, Arianna; Tofalo, Rosanna (Frontiers in Microbiology, 2024)
The cheese microbiota is very complex and is made up of technologically-relevant, spoilage, opportunistic and pathogenic microrganisms. Among them lactic acid bacteria and yeasts are the main ones. One of the most interesting dairy yeasts is Kluyveromyces marxianus because of its technological properties including the ability to produce aroma compounds.Methods: This study investigated the contribution of Kluyveromyces marxianus to the gross composition and aroma profile of cow cheeses. Experimental cheeses were prepared by inoculating a co-culture of K. marxianus FM09 and a commercial strain of Lacticaseibacillus casei and compared with cheeses obtained with only L. casei. The gross composition was determined by a FoodScan TM 2 Dairy Analyser, and free amino acids were evaluated at 507 nm after reaction with Cd-ninhydrin. The volatile organic compounds were extracted by head-space solid phase micro-extraction and analyzed by gas chromatography-mass spectrometry coupled with odor activity values. qRT-PCR was applied to determine the expression of genes involved in esters synthesis and degradation.The inoculation of K. marxianus induced an increase of pH and a reduction of protein content of cheeses, in agreement with the stronger proteolysis detected in these cheeses. K. marxianus influenced the content of aroma compounds both quantitatively and qualitatively. In particular, an increase of higher alcohols, esters and organic acids was observed. Moreover, 12 compounds were detected only in cheeses obtained with the co-culture. These differences were in agreement with the odor threshold values (OAV). In fact, only 11 compounds showed OAV>1 in cheeses obtained with the commercial strain, and 24 in those obtained with the co-culture. The qPCR analysis revealed an over expression of ATF1, EAT1, and IAH1 genes.K. marxianus could act as an important auxiliary starter for cheese production through the development and diversification of compounds related to flavor in short-aged cow cheeses.